Edukasi dan Pemeriksaan Kesehatan Gigi Siswa SMAN 2 Sidrap Menuju Indonesia Bebas Karies 2030 - Yulistina, Yulistina; Zulkaidah, Utari; Dirman, Rezki; Sunandar, Sunandar; Zainab, Zainab (Universitas Pahlawan Tuanku Tambusai, 2025)
Dental caries remains one of the major oral health problems among adolescents. Lack of knowledge and poor oral hygiene habits greatly contribute to the high incidence of caries. This community service activity was carried out to increase students’ understanding and awareness at SMAN 2 Sidrap about the importance of maintaining oral and dental health in support of the Caries-Free Generation 2030 program. The activities included interactive counseling, demonstrations of proper tooth-brushing techniques, and oral health examinations. The results showed an improvement in students’ knowledge and attitudes toward maintaining oral hygiene, as well as several detected cases of caries that required further treatment. This program is expected to foster healthy living behavior and serve as a concrete step toward realizing a caries-free young generation.